Năng suất của doanh nghiệp vừa và nhỏ Việt Nam: Vai trò của hoạt động xuất khẩu - Ngô Hoàng Thảo , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
By using two-step system GMM method, the study tests the learning mechanism by exporting hypothesis of small and medium-sized enterprises (SMEs) in Vietnam from 2005 to 2013. The results show that export has a positive impact on total factor productivity at firm level. Moreover, the study finds reasons for an appearance of learning mechanism by exporting: (i) exporting firms receive technological transfers from developed countries; and (ii) exporting firms have enough capabilities to absorb knowledge generated by exporting.
Keywords: Export; Total factor productivity; Small- and medium-sized enterprises; Learning by exporting; Export destination